Effectiveness of engaging religious leaders in maternal health education for improving maternal health service utilization in Ethiopia: cluster randomized controlled trial - Sadore, Abinet Arega; Kebede, Yohannes; Birhanu, Zewdie (Frontiers in Public Health, 2024)
Introduction High mortality rates for pregnant women and their new-borns are one of Africa’s most intractable public health issues today, and Ethiopia is one of the countries most afflicted. Behavioral interventions are needed to increase maternal health service utilizations to improve outcomes. Hence, this trial aimed to evaluate effectiveness of trained religious leaders’ engagement in maternal health education on maternal health service utilization. Methods The study employed a cluster-randomized controlled community trial that included baseline and end-line measurements. Data on end points were gathered from 593 pregnant mothers, comprising 292 and 301 individuals in the intervention and control groups, respectively. In the intervention group, the trained religious leaders delivered the behavioral change education on maternal health based on intervention protocol. Unlike the other group, the control group only received regular maternal health information and no additional training from religious leaders. Binary generalized estimating equation regression analysis adjusted for baseline factors were used to test effects of the intervention on maternal health service utilization. Results Following the trial’s implementation, the proportion of optimal antenatal care in the intervention arm increased by 21.4% from the baseline (50.90 vs. 72.3, p ≤ 0.001) and the proportion of institutional delivery in the intervention group increased by 20% from the baseline (46.1% vs. 66.1%, p ≤ 0.001). Pregnant mothers in the intervention group significantly showed an increase of proportion of PNC by 22.3% from baseline (26% vs. 48.3%, p ≤ 0.001). A statistically significant difference was observed between in ANC4 (AOR = 2.09, 95% CI: 1.69, 2.57), institutional delivery (AOR = 2.36, 95% CI: 1.94, 2.87) and postnatal care service utilization (AOR = 2.26, 95% CI: 1.79, 2.85) between the intervention and control groups. Conclusion This research indicated that involving religious leaders who have received training in maternal health education led to positive outcomes in enhancing the utilization of maternal health services. Leveraging the influential position of these religious leaders could be an effective strategy for improving maternal health service utilization. Consequently, promoting maternal health education through religious leaders is advisable to enhance maternal health service utilization. Clinical trial registration: [https://clinicaltrials.gov/], identifier [NCT05716178].